Complete closure utilizing titanium clips minimizes delayed postpolypectomy bleeding after colorectal endoscopic mucosal resection: a retrospective analysis - Wei-Feng Li; Bing Lai; Li Lv; Xi-Qiu Yu; Jia-Le Fan; Zhi-Wei Zhou; Jing-Wen Xu; Ruo-Yu Gao; Ze-Ming Chen; Bi-Xia Xu (Therapeutic Advances in Gastroenterology)
Background: Delayed postpolypectomy bleeding (DPPB) constitutes one of the most prevalent complications following endoscopic mucosal resection (EMR) for colonic polyps and can be life-threatening. It has been affirmed that prophylactic clip closure can effectively diminish the risk of DPPB for colonic polyps exceeding 20 mm in the right half of the colon after EMR. Nevertheless, there remains controversy regarding whether prophylactic clip closure can prevent postoperative bleeding for polyps measuring less than 20 mm. To date, no literature has reported whether the complete closure of titanium clips following EMR for colorectal polyps ⩽20 mm can effectively prevent delayed bleeding. Objectives: The aim of this study is to determine whether complete closure can prevent delayed postoperative bleeding and analyze the related factors that might influence delayed postoperative bleeding. Design: In this retrospective study, a total of 1259 colorectal polyps detected in 1025 patients between January 2020 and October 2024 were evaluated for EMR. Methods: Univariate and logistic regression analyses were conducted to assess patient-related, polyp-related, and procedure-related factors. Results: DPPB was observed in 37 patients, representing an incidence rate of 3.6%. Logistic regression analysis indicated that male (odds ratio, 3.870; 95% confidence interval (CI), 1.594–9.396; p  = 0.003), presence of large polyps (OR, 1.158; 95% CI, 1.044–1.285; p  = 0.006), and partial closure (OR, 5.447; 95% CI, 2.250–13.186; p  < 0.001) are significant risk factors for the development of DPPB. Conclusion: Male, polyp size, and partial closure have been identified as potential risk factors for the development of DPPB. While gender and polyp size are immutable factors, partial closure is particularly associated with an increased risk of DPPB. Therefore, it is imperative to ensure complete closure of the wound following EMR to minimize the occurrence of DPPB.